2005
DOI: 10.1021/ol0476624
|View full text |Cite
|
Sign up to set email alerts
|

Partial Reduction of Pyridinium Salts as a Versatile Route to Dihydropyridones

Abstract: [reaction: see text] The addition of two electrons to a pyridinium salt turns it into a nucleophile. The intermediate generated by the reduction of such salts can be reacted successfully with a range of different electrophiles (acids, alkyl halides, and carbonyl compounds) and the intermediate hydrolyzed in situ to provide a wide range of dihydropyridones. Each position on the dihydropyridone ring is then accessible using standard synthetic manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Conjugate addition of hexylcuprate under the modified Donohoe protocol 38 proceeded in a diastereoselective manner from the pseudoequatorial position at C(2), and this was followed by basic hydrolysis to give (±)-cylindricine C [(±)-5] as a 7:1 mixture of diastereomers.…”
Section: Review Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugate addition of hexylcuprate under the modified Donohoe protocol 38 proceeded in a diastereoselective manner from the pseudoequatorial position at C(2), and this was followed by basic hydrolysis to give (±)-cylindricine C [(±)-5] as a 7:1 mixture of diastereomers.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…47 The construction of the azadecalin (AB ring) framework commenced with regioselective addition of the Grignard reagent to electron-deficient pyridinium salt 105. 38,48 The reaction of N-(3,4-dimethoxybenzyl)pyridinium salt 105 with 4-chlorobutylmagnesium bromide proceeded by regioselective addition at the C 10…”
Section: From a Ringmentioning
confidence: 99%
“…23 However, it was found that reduction of the pyridinium salts sometimes led to variable results on reaction scale-up. As an alternative, in order to access the same products, the nucleophilic addition to a pyridinium salt was considered to be an attractive alternative.…”
Section: Nucleophilic Addition To Pyridinium Saltsmentioning
confidence: 99%
“…Alkyl halides, tosylates, triflates, and so on react readily with pyridines by an S N 2 reaction to give alkylpyridinium salts (Scheme 16.47) [150]. Bulky substituents around the nitrogen ring atom, or tertiary halides or related compounds cause an increase in the competing elimination reaction giving rise to the corresponding alkene and tertiary salts.…”
Section: Reactions With Halides and Related Compoundsmentioning
confidence: 99%